2019
DOI: 10.1111/mec.15143
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic resilience, symbiont shuffling, and vulnerability to recurrent bleaching in reef‐building corals

Abstract: As climate change progresses and extreme temperature events increase in frequency, rates of disturbance may soon outpace the capacity of certain species of reef‐building coral to recover from bleaching. This may lead to dramatic shifts in community composition and ecosystem function. Understanding variation in rates of bleaching recovery among species and how that translates to resilience to recurrent bleaching is fundamental to predicting the impacts of increasing disturbances on coral reefs globally. We trac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 65 publications
6
40
0
1
Order By: Relevance
“…Modules also show natural fluctuations involved in homeostasis during nonstressful events and how certain temperature thresholds produce a strong but temporary reaction relating to the unfolded protein response (Ruiz-Jones & Palumbi, 2017). A similar set of modules showed that experimental heat stress and response during recurrent bleaching was similar (Thomas et al, 2019). Correlations between transplant site, origin and various photosynthetic responses have also been documented for WGCNA modules in Porites astreoides (Kenkel & Matz, 2016), which were used to examine differences in plasticity of gene response.…”
Section: Coexpression Networkmentioning
confidence: 86%
See 2 more Smart Citations
“…Modules also show natural fluctuations involved in homeostasis during nonstressful events and how certain temperature thresholds produce a strong but temporary reaction relating to the unfolded protein response (Ruiz-Jones & Palumbi, 2017). A similar set of modules showed that experimental heat stress and response during recurrent bleaching was similar (Thomas et al, 2019). Correlations between transplant site, origin and various photosynthetic responses have also been documented for WGCNA modules in Porites astreoides (Kenkel & Matz, 2016), which were used to examine differences in plasticity of gene response.…”
Section: Coexpression Networkmentioning
confidence: 86%
“…This difference could be due to acclimatization, but the authors could not rule out symbiont shuffling or differential mortality leading to a higher proportion of resilient corals in the second event (Hughes et al, ). Studies that follow individual corals can conclusively rule out differential mortality, such as (Fisch, Drury, Towle, Winter, & Miller, ), who documented a substantial minority of surveyed colonies which experienced less severe visual bleaching in recurrent bleaching events that could be attributed to acclimatization (but see Thomas, López, Morikawa, & Palumbi, ).…”
Section: Ecological Signatures Of Acclimatization In Coralsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcriptional resilience was an indicator to predict stress tolerance (Franssen et al, 2011). For example, the study on the resilient patterns of recurrent bleaching on corals (genus Acropora) showed that the resilience capacity after bleaching strongly contributed to the sensitivity to future bleaching, and the species A. gemmifera with a fast recovery speed resulted in a high level of survival under repeated heat extremes (Thomas et al, 2019). Similarly, the transcriptional resilience in this study adds evidence on the adaptative response against recurrent stresses and should be functional in adaptative homeostasis simultaneously.…”
Section: Dynamic Response Of the Antioxidant Defense System Under Colmentioning
confidence: 99%
“…This demonstrates that although expressed coral isoforms outnumber symbiont isoforms, highly expressed symbiont isoforms were expressed significantly more than coral isoforms. Few gene expression studies report read count statistics for individual isoforms or genes; however, one recent study similarly found thousands of contigs (contiguous gene sequences) that surpassed a minimum read count threshold to compare the transcriptomic response to recurrent bleaching events between two acroporid coral species (Thomas, López, Morikawa, & Palumbi, ).…”
Section: Resultsmentioning
confidence: 99%